THE INFLUENCE OF MARKETING MIX ON SATISFACTION CUSTOMERS AT NAFIYAH STORE BOUTIQUE PALU CITY - Ilmawati (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
The purpose of this study was to determine the influence of the marketing mix on customer satisfaction at the Nafiyah Store Boutique in Palu City. The number of samples in this study were 88 respondents. The analytical method used in this research is causal descriptive research. By using multiple regression analysis, which is an analysis to see how far the influence of customer satisfaction at the Nafiyah Store Boutique in Palu City. product, price, promotion and location have a significant effect on customer satisfaction interest at the Nafiyah Store Boutique, Palu City. The product has a significant effect on customer satisfaction interest at the Nafiyah Store Boutique in Palu City. Price has a significant effect on customer satisfaction interest at the Nafiyah Store Boutique in Palu City. Promotion has a significant effect on customer satisfaction interest at the Nafiyah Store Boutique in Palu City. location has a significant effect on customer satisfaction interest at the Nafiyah Store Boutique, Palu City.